A Moderating Effect of Leadership between Culture and Creativity - Na Keeree, Pratsanee; Pianluprasidh, Piyatida; Abdul Wahid, Khalid; Nicholas Nyoni, Mihlayifani (Journal of Business, Innovation and Sustainability (JBIS), 2026)
The study seeks to establish the influence of organisational culture on creativity, as the development of employees’ creativity depends greatly on a conducive organisational culture. Also, an investigation of the impact of the moderating effect of leadership organisational culture and creativity. Studies have shown that leadership has an impact on both creativity, and organisational culture. The purpose then is to show how that acts as a moderating between organisational culture and creativity. A cross-sectional sample was taken from the top 20 Thai institutions according to SCImago Institutions Ranking’s innovation rankings for 2022. 250 employees from those universities received the questionnaires, and 183 of them responded. The research employed structural equation modelling using Smart Partial Least Squares (Smart PLS). According to the findings, both market culture and clan culture were moderated by participative leadership. The hierarchical culture, however, was not moderated by participative leadership. The research demonstrates that organisational culture is crucial for innovation and leadership, particularly participative leadership. The study was limited to Thai HEIs which in turns limits the outcomes to the information based on these institutions. Further study can be conducted on lower ranking institutions, as well as different societies to give a fuller picture. The study was also limited to across sectional quantitative study. Further study can be conducted using a longitudinal qualitative approach to gather more intrinsic detail on the subject. The study makes a substantial contribution to the body of literature by demonstrating a novel moderating effect that suggests participatory leadership may stimulate organisational innovation in HEIs. Prior to this study, the discovery was unknown. As a consequence, it will effectively close the gap in the research on organisational innovation by determining whether or not participatory leadership is possible in Thai HEIs.